Disturbance‐accelerated succession increases the production of a temperate forest. Issue 7 (11th August 2021) - Gough, Christopher M.; Bohrer, Gil; Hardiman, Brady S.; Nave, Lucas E.; Vogel, Christoph S.; Atkins, Jeff W.; Bond‐Lamberty, Ben; Fahey, Robert T.; Fotis, Alexander T.; Grigri, Maxim S.; Haber, Lisa T.; Ju, Yang; et al.
Abstract: Many secondary deciduous forests of eastern North America are approaching a transition in which mature early‐successional trees are declining, resulting in an uncertain future for this century‐long carbon (C) sink. We initiated the Forest Accelerated Succession Experiment (FASET) at the University of Michigan Biological Station to examine the patterns and mechanisms underlying forest C cycling following the stem girdling‐induced mortality of >6, 700 early‐successional Populus spp. (aspen) and Betula papyrifera (paper birch). Meteorological flux tower‐based C cycling observations from the 33‐ha treatment forest have been paired with those from a nearby unmanipulated forest since 2008. Following over a decade of observations, we revisit our core hypothesis: that net ecosystem production (NEP) would increase following the transition to mid‐late‐successional species dominance due to increased canopy structural complexity. Supporting our hypothesis, NEP was stable, briefly declined, and then increased relative to the control in the decade following disturbance; however, increasing NEP was not associated with rising structural complexity but rather with a rapid 1‐yr recovery of total leaf area index as mid‐late‐successional Acer, Quercus, and Pinus assumed canopy dominance. The transition to mid‐late‐successional species dominance improved carbon‐use efficiency (CUE = NEP/gross primary production) as ecosystem respiration declined. Similar soil respiration rates in control and treatment forests, along with species differences in leaf physiology and the rising relative growth rates of mid‐late‐successional species in the treatment forest, suggest changes in aboveground plant respiration and growth were primarily responsible for increases in NEP. We conclude that deciduous forests transitioning from early to middle succession are capable of sustained or increased NEP, even when experiencing extensive tree mortality. This adds to mounting evidence that aging deciduous forests in the region will function as C sinks for decades to come.